Influence of physico-chemical factors on the zooplankton population of Bostami pond of Chittagong (Bangladesh Journal of Zoology, 2016)
The study was conducted on the influence of physico-chemical factors on the zooplankton of Bostami pond in Chittagong city for a period of one year from February 2013 to January 2014. During this study the water depth varied from 1.54 to 2.53 m, water temperature 24.5 to 32.6°C, conductivity 0.234 to 0.297 mS, turbidity 26.55 to 33.41 ntu, light intensity 27 to 39.5 lux, total dissolved solids 161 to 191 ppm, pH 7.02 to 7.79, dissolved oxygen 3.4 to 5.73 ppm, free carbon dioxide 2.82 to 5.85 ppm, and calcium 25.08 to 43.03 ppm. It was found that the temperature was less during February 2013 and gradually increased up to June 2013. Then with a break in July it gradually decreased until the next January 2014. More or less reverse data observed for the monthly variation of conductivity, total dissolved solids and calcium. Free carbon dioxide is inversely related with water depth and pH. In total 19 species of zooplankton were identified, where 16 rotifera were the dominant followed by two copepods and one cladoceran. Among these, Brachionus diversicornis, B. angularis, B. quadridentatus, B. falcatus, B. calyciflorus, B. forficula, B. caudatus, Platyias patulus, Keratella cochlearis, Lecane luna, Trichocerca cylindrica, Polyarthra vulgaris, Asplanchna priodonta, A. brightwelli, Filinia longiseta, F. terminalis, Mesocyclops leuckarti, Cyclops varicans rubellus and Moina brachiata were the most common species in the pond throughout the year. Abundance of phytoplankton and zooplankton indicated that the nutrient quality of the pond water was good. The total phytoplankton varied from 842 to 2223 individuals/l and total zooplankton 187 to 494 individuals/l; with rotifera 105 to 266 individuals/l, copepoda 43 to 135 individuals/l and cladocera from 39 to 115 individuals/l throughout the year. Plankton abundance and physico-chemical characteristics of the Bostami pond indicate that the pond is eutrophic in nature.Bangladesh J. Zool. 44(1): 73-87, 2016